Piano Sonatas. Braunschweig: Henry Litolff; Paris: Enoch Frères et Costallat. [Newman 67] - Beethoven, Ludwig van, 1770-1827 (composer):::Creator::::::::::::; Germer, Heinrich, 1837-1913 (editor):::Contributor::::::::::::; Lussy, Mathis, 1828-1913 (translator):::Contributor:::::::::::: (Braunschweig and Paris; Henry Litolff's Verlag and Enoch Frères et Costallat, 2024)
Piano sonatas edited by Heinrich Germer and published by Henry Litolff's Verlag, with French translations of Germer's preface and remarks on each sonata.